The Influence of Principal Leadership and School Culture on The Performance of PPKn Teachers in State High School in Pekanbaru City - Rhany, Olivia Chintya; Marhadi, Hendri; Aibonotika, Arza (CV. Tripe Konsultan, 2024)
Education is the main means in the formation and creation of quality human resources, both through education at home and through education at school. Without education, it will be difficult to produce good quality human resources that can determine the future of the nation itself. This study aims to analyze the influence of principal leadership and school culture on the performance of Pancasila and Citizenship Education (PPKn) teachers in State Senior High Schools throughout Pekanbaru City. The research method used is a quantitative approach with multiple linear regression analysis. The research sample consisted of 51 PPKn teachers selected using saturated sampling techniques. The results of the study showed that principal leadership and school culture had a positive and significant effect on teacher performance, with principal leadership having a greater contribution than school culture. Simultaneously, both variables contributed 79.4% to improving teacher performance. Based on these findings, it is recommended that principals implement a more participatory and transformative leadership style, and strengthen a collaborative and innovative school culture in order to improve the quality of learning.